Microtensile Bond Strength of Composite Resin Following the Use of Bromelain and Papain as Deproteinizing Agents on Etched Dentin: An In Vitro Study - Khatib, Mohd Sibghatullah (Int J Clin Pediatr Dent, 2020)
AIM AND OBJECTIVES: The aim of this study was to evaluate and compare the deproteinizing effect of sodium hypochlorite, bromelain, and papain on microtensile bond strength of composite resin to etched dentin. MATERIALS AND METHODS: Eighty freshly extracted permanent molars were wet grounded into a flat surface using a diamond disk to expose the superficial dentinal surface. Teeth were etched with 37% phosphoric acid for 15 seconds and rinsed with water and blot dried. Teeth were divided into four groups (n = 20) based on the method of dentin deproteinization. Group I: only etching; group II: deproteinized with 5.25% sodium hypochlorite for 1 minute; group III: deproteinized with 8% bromelain enzyme for 1 minute; and group IV: deproteinized with 8% papain enzyme for 1 minute. All the samples were washed off with distilled water to remove deproteinizing agents. Sample surfaces were blot dried and bonding of the dentin surface was performed and restored with light cure bulk fill composite. Samples were stored in distilled water (37°C/24 hours) and thermocycled. Then, the teeth were longitudinally sectioned and individually fixed to a sectioning block using acrylic resin. The block was mounted on hard tissue microtome and sectioned to get one to three slabs of 1 mm thick sections. The beam was then attached to a custom-made jig using screws subjected to the Instron universal testing machine. A tensile load was applied at a crosshead speed of 0.5 mm/minute until the beam fractured. RESULTS: Higher mean bond strength was recorded in group IV followed by group III, group II, and group I, respectively. Group III presented a statistically significant highest mean score compared to other study groups with group I and group II (p < 0.001), followed by group IV having significantly higher mean score compared to group I and group II (p < 0.001) and finally a significant difference was observed between group II and group I (p < 0.001). However, the mean microtensile bond strength score did not differ significantly between group III and group IV (p = 0.20). CONCLUSION: Within the limitations of this present in vitro study, the following conclusions were drawn. The microtensile bond strength of dentine tested in various deproteinizing agents is as follows: 8% bromelain > 8% papain > 5.25% NaOCl > control group. Naturally occurring deproteinizing agents, such as bromelain and papain, used in this study have resulted in greater bond strength values when compared to that of traditionally used chemical agent such as NaOCl. HOW TO CITE THIS ARTICLE: Khatib MS, Devarasanahalli SV, Aswathanarayana RM, et al. Microtensile Bond Strength of Composite Resin Following the Use of Bromelain and Papain as Deproteinizing Agents on Etched Dentin: An In Vitro Study. Int J Clin Pediatr Dent 2020;13(1):43–47.